Pemberdayaan Desa Gunung Kijang: Sinergi Masyarakat Kepulauan Menuju Kemandirian dan Kesejahteraan - Cindy Verindica Gorat; Ruhil Amani; Chiska Hoseana Manalu; Renalda Pratiwi; Intan Wulandari; Novia Putri Ramadhania; Mega Aulia Putri; Batubara Batubara; Alga Raya Khasana; Hadli Lidya Rikayana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This community service program in Gunung Kijang Village, Bintan Regency, Riau Islands Province, was designed to strengthen local empowerment through the synergy of education, economy, agriculture, and social participation. The activities consisted of four initiatives: workshops on Canva-based learning media for teachers, digital marketing training and social media account creation for MSMEs, participatory mapping of challenges and potentials of local food businesses, and smart farming education using soil moisture sensors to introduce efficient irrigation technology. The results showed significant achievements across sectors. In education, teachers improved their technological skills and created interactive media that enhanced student motivation. In the economic sector, MSMEs adopted digital promotion strategies, leading to wider market reach and sales. The participatory mapping revealed obstacles such as licensing, packaging, and financial literacy, while also identifying opportunities for product diversification using local resources. In agriculture, farmers were introduced to water-saving irrigation technology that improved efficiency and supported environmentally friendly practices. On the social side, community institutions such as PKK, Karang Taruna, and farmer groups played an important role in strengthening solidarity and expanding collaboration. Overall, the program proved that integrating digital literacy, technological innovation, and community participation can accelerate rural independence while fostering sustainable welfare for island communities.